35 IPGM Sultan Mizan Campus students participate in Raspberry Pi Programming 2024 - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 2 June 2024 – Recently, 35 students from the Institute of Teacher Education Malaysia (IPGM), Sultan Mizan Campus, Besut, Terengganu participated in the Raspberry Pi 2024 Programming to improve programming skills at the STEM Laboratory, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).